2021
DOI: 10.31662/jmaj.2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens in Vasculitis: Is It Really Idiopathic?

Abstract: Vasculitis is an autoimmune disease characterized by the infiltration of leukocytes in blood vessels. An increasing number of studies on human and animal models have implicated various microorganisms in the pathogenesis of vasculitis. Previous studies have shown the presence of infectious agents, including viruses, bacteria, and fungi, in diseased vessels. However, despite continued research, the link between infection and vasculitis is not fully understood, possibly owing to the lack of appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…On the other hand, excessively activated leukocytes, including lymphocytes, macrophages, and neutrophils, damage the vessels and aggravate inflammation 12 . While the etiology of vasculitis remains incompletely understood, an increasing number of animal and human studies have suggested that it is associated with a variety of pathogenic agents including bacteria, viruses, and fungi 4 . Previous studies have indicated that viruses relate to small-vessel vasculitis in many cases, whereas bacterial infections cause vasculitis in all sizes of vessels 24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, excessively activated leukocytes, including lymphocytes, macrophages, and neutrophils, damage the vessels and aggravate inflammation 12 . While the etiology of vasculitis remains incompletely understood, an increasing number of animal and human studies have suggested that it is associated with a variety of pathogenic agents including bacteria, viruses, and fungi 4 . Previous studies have indicated that viruses relate to small-vessel vasculitis in many cases, whereas bacterial infections cause vasculitis in all sizes of vessels 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the nine different genetic variants of the SEN virus (A to I), the most predominant genotypes are SEN virus D and H, which are typically found in patients with non-A-E hepatitis 26 . HBV is associated with cryoglobulinemic small-vessel vasculitis and polyarteritis nodosa (PAN), and the relationship between PAN and HBV has been often reported 4 . Approximately 5% of patients with HCV-associated mixed cryoglobulinemia develop cryoglobulinemic vasculitis, as a consequence of the deposition of immune complex (IC) in small vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV infection is associated with vasculitis affecting the aorta and major branches, and PAN-like forms have also been described. Chronic active EBV infection is linked to medium- to large-vessel vasculitis, with coronary artery aneurysms as a typical complication 69 , 70 ; it is also linked with KD 71 . A broad spectrum of coronary changes including aneurysms, chronic vasculitis, and luminal narrowing due to myofibroblastic proliferation, have been described in a young adult suffering from KD associated with Parvovirus 19 infection 72 .…”
Section: Coronary Arteritismentioning
confidence: 99%